(untitled) (The Chittagong University Journal of Science, 2023)
Global warming due to greenhouse gas (GHG) emission is the most challenging issue nowadays. Life Cycle Assessment on different materials contributes to this by articulating greenhouse gas (GHG) emission in various stages. This study quantifies GHG emissions from the iron recycling process of Chittagong City Corporation (CCC). It collects technical data through an on-site visit and questionnaire survey to each of the selected processing industries and waste depots by a semi-structured questionnaire. The study shows that total GHG emission is 314 kgCO2-eq/ton of scraps in waste depots. Processing industries contribute GHG of 605.3 kgCO2-eq/ton for billet production and 80.3 kgCO2-eq/ton for rod production from electricity consumption. Moreover, these industries produce GHG of 0.875 kgCO2-eq/ton for billet production and 2766.11 kg CO2-eq/ton for rod production from natural gas consumption. The study contributes to global warming reduction practices from iron waste recycling in Bangladesh. The Chittagong Univ. J. Sci. 44(1): 1-16, 2022